Alimentation et nutrition dans les départements et régions d'Outre-mer/Food and nutrition in the French overseas departments and regions - Méjean, Caroline; Debussche, Xavier; Martin-Prével, Yves; Réquillart, Vincent; Soler, Louis-Georges; Tibère, Laurence (Expertise collégiale, 2020)
The nutritional situation and food consumption habits of the inhabitants of the French overseas territories pose very specific socio-economic and public health-related challenges. Apart from having to deal with a prevalence of overweight, obesity and diabetes more significant than that of the French mainland, these territories are also undergoing both rapid and profound demographic, nutritional and food-related transformations leading to changes in lifestyle which could result in insufficient physical activity as well as uneven food consumption. Within this context, the Directorate General of Health has charged the French Research Institute for Development (IRD) to conduct a multidisciplinary scientific expert overview of the nutritional situation and food consumption of the inhabitants of the French overseas territories in order eventually to lend a specific orientation to the National Nutritional Health Plan for these areas. The scope of the overview includes Guadeloupe, French Guiana, Martinique, Mayotte and La Réunion and the objective is to provide a picture of the differences and similarities between the various territories based on available data. To this end, the IRD has assembled a multidisciplinary committee of experts composed of epidemiologists, nutritionists, doctors specialising in public health issues, economists, endocrinologists, specialists in diabetic ailments and sociologists.